2014
DOI: 10.1007/s10072-014-1689-5
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of central TRPV1 receptors in pentylenetetrazole and amygdala-induced kindling in male rats

Abstract: Transient receptor potential vanilloid 1 (TRPV1) is a non-selective cation channel that is involved in modulation of diverse physiological processes. The role of this receptor in epilepsy has not been studied well. Therefore, we investigated the role of central TRPV1 receptors on the development of pentylenetetrazole (PTZ) and amygdala-induced kindling in rats. Male Wistar rats received subconvulsive dose of PTZ intraperitoneally, every other day. TRPV1 receptor agonist, OLDA and its antagonist, AMG-9810 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
3
25
0
1
Order By: Relevance
“…However, the prolonged seizure and afterdischarge duration of TRPV1 KO mice after the kindling process indicates that TRPV1 might contribute to seizure termination once a hyperexcitable neuronal network has been formed in the epileptic brain. In line with this idea is the recent study of Shirazi et al (2014) who reported reduced electrographic seizure duration in fully-kindled mice when treated with a TRPV1 antagonist. However, this assumption needs to be studied in more detail, also considering that pharmacological antagonism did not exert a comparable effect on the post-kindling seizure durations.…”
Section: Seizures Increase Cb1r Density In the Pyramidal Cell Layer Omentioning
confidence: 61%
See 1 more Smart Citation
“…However, the prolonged seizure and afterdischarge duration of TRPV1 KO mice after the kindling process indicates that TRPV1 might contribute to seizure termination once a hyperexcitable neuronal network has been formed in the epileptic brain. In line with this idea is the recent study of Shirazi et al (2014) who reported reduced electrographic seizure duration in fully-kindled mice when treated with a TRPV1 antagonist. However, this assumption needs to be studied in more detail, also considering that pharmacological antagonism did not exert a comparable effect on the post-kindling seizure durations.…”
Section: Seizures Increase Cb1r Density In the Pyramidal Cell Layer Omentioning
confidence: 61%
“…Neonatal TRPV1 deficient mice are less susceptible to PTZ-induced seizures following hyperthermia (Kong et al, 2014). Moreover, agonists like capsaicin and OLDA enhanced epileptiform activity, whereas antagonists like capsazepine and AMG9810 abolished these effects (Bhaskaran and Smith, 2010;Gonzalez-Reyes et al, 2013;Shirazi et al, 2014). Capsazepine is a competitive antagonist of capsaicin with species-specific activity (McIntyre et al, 2001;Savidge et al, 2002).…”
Section: Seizures Increase Cb1r Density In the Pyramidal Cell Layer Omentioning
confidence: 98%
“…However, it remains unclear whether the increased TRPV1 expression described reflects an uninvolved and downstream consequence of disease or an integral part of the process. The preclinical literature describing TRPV1 involvement in epilepsy is conflicted where studies suggest no involvement [126,127], a proconvulsant effect, or an anticonvulsant effect of TRPV1 activation [128][129][130][131][132][133][134]. Overall, a larger number of studies suggest that the consequences of TRPV1 activation in epilepsy are detrimental which, given the large number of validated studies asserting overwhelmingly anticonvulsant effects of CBD in these animal models, suggests that TRPV1 activation by CBD is not part of its antiepileptic mechanism of action.…”
Section: Cbd Ion Channel Targets In Epilepsymentioning
confidence: 99%
“…Very recently, the involvement of TRPV1 in the modulation of learning and memory processes by stress was evaluated in mice by assessing the effects of OLDA on long-term potentiation (LTP) of the lateral nucleus of the amygdala (LA) induced by highfrequency stimulation of external capsule fibers. Seizures were instead reduced by the TRPV1 antagonist AMG-9810, which counteracted the proconvulsant effect of OLDA amygdala-induced kindling [36]. On the other hand, a short period of acute stress, i.e., exposure to a forced swim test significantly impaired LA-LTP; and OLDA rescued LA-LTP in control but not TRPV1-deficient mice [34].…”
Section: Trpv1-and/or Cb1-mediated Actionsmentioning
confidence: 94%